The Role of Cultural Values in National-Level Innovation: Evidence from 106 Countries. (October 2022) - Bonetto, Eric; Pichot, Nicolas; Adam-Troïan, Jaïs
Innovation constitutes a key factor for the economy and the competitiveness of societies. Using the Hofstede model of national culture, previous studies investigated the influence of different cultural dimensions on national-level innovation. These studies provided for mixed evidence regarding the influence and weight of each cultural dimension in innovation. By considering possible explanations for these inconsistent results, the present study ( N = 106 countries) showed that only two cultural dimensions seem to be consistently associated with innovation. Cultures that view change as necessary (long-term oriented) and are more accepting of norm violations (displaying low uncertainty avoidance) tend to promote innovation. These results shed new light on the way cultural tightness and social regulation processes can affect innovative behaviors.